Psychometric Properties and Factor Structure of the Patient Health Questionnaire-9 as a Screening Tool for Depression Among Ecuadorian College Students - López-Guerra, Víctor Manuel; López-Núñez, Carla; Vaca-Gallegos, Silvia L.; Torres-Carrión, Pablo V. (Frontiers in Psychology, 2022)
Background: The Patient Health Questionnaire-9 (PHQ-9) is the most well-known self-report measure to screen for depressive symptomatology, although discerning which is the factor structure that represents the best fit remains a challenge. Objective: The aim of this study was to analyze the psychometric properties and factorial structure of the Spanish version of the PHQ-9 in a large sample of Ecuadorian college students. Methods: A total of 5,394 students (M = 22.03 years; SD = 3.05; 54.8% female) from three Ecuadorian universities were surveyed using a computerized questionnaire within a 4-week assessment period. The PHQ-9 was tested for factorial structure, reliability, and correlations with other mental health-related measures. Results: The hierarchical model that included a general factor and three nested factors had a better fit, and such a hierarchical structure remained invariant across sex and age. Total omega value (ω) was 0.90 for the total scale and hierarchical omega values (ωh) were 0.68 for the general factor, as well as 0.34, 0.38 and 0.44 for the respective nested factors (somatic, cognitive/affective, concentration/motor). Moreover, PHQ-9 scores were significantly higher among women, although effect sizes of comparison of those sex differences were very small. Finally, the PHQ-9 scores correlated with multiple mental health indicators (psychological inflexibility, loneliness, stress, and satisfaction with life). Discussion: The Spanish version of the PHQ-9 showed good psychometric properties among Ecuadorian college students. The hierarchical structure showed the best fit for the data, including not only a dominant general factor, but also the somatic, cognitive/affective and concentration/motor subcomponents. In conclusion, the PHQ-9 tool seems to represent an easy-to-implement screening questionnaire to design preventive programs for those Ecuadorian college students at risk of developing depressive disorders.